STRATEGIC UTILIZATION OF DIGITAL LEARNING PLATFORMS IN THE ERA OF INDEPENDENT CURRICULUM - Welsi Damayanti; Siminto; Muhammad Arsyad; Eyad Saleh Bani-Domi (International Journal of Teaching and Learning, 2024)
The advent of the Independent Curriculum era, exemplified by curriculum Kurikulum Merdeka in Indonesia, has brought about a paradigm shift in education, emphasizing autonomy, flexibility, and relevance. In this transformative landscape, the strategic utilization of digital learning platforms emerges as a pivotal factor in enhancing teaching and learning outcomes. This paper explores the intersection of digital learning platforms and the Independent Curriculum, aiming to elucidate effective strategies for their integration. Drawing on a comprehensive review of literature, this study examines the principles underpinning the Independent Curriculum and the potential benefits of digital learning platforms within this context. Key findings highlight the importance of flexibility, adaptability, and local relevance in curriculum design, as well as the transformative role of digital technologies in facilitating personalized learning experiences and fostering collaboration. The study identifies several strategic approaches for educators and policymakers to harness the potential of digital learning platforms effectively. These include promoting professional development initiatives, fostering collaborative partnerships, addressing infrastructure gaps, and ensuring equitable access to digital resources.